2021
DOI: 10.21037/atm-21-871
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chinese herbal medicine combined with Western medicine on deferring dialysis initiation for nondialysis chronic kidney disease stage 5 patients: a multicenter prospective nonrandomized controlled study

Abstract: Wu et al. CHM on deferring dialysis initiation for stage 5 CKD patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In our study, we found that circ_0139658 increased expression in RA‐FLSs; functionally, silencing of circ_0139658 impaired the proliferation, migration, invasion, and inflammation in RA‐FLSs. To date, the combination of Chinese herbal medicine and Western medicine has gained great popularity in the treatment of diseases (Wu et al., 2021). Here, we proved that circ_0139658 overexpression abolished the suppressing effects of Brucine on RA‐FLS dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that circ_0139658 increased expression in RA‐FLSs; functionally, silencing of circ_0139658 impaired the proliferation, migration, invasion, and inflammation in RA‐FLSs. To date, the combination of Chinese herbal medicine and Western medicine has gained great popularity in the treatment of diseases (Wu et al., 2021). Here, we proved that circ_0139658 overexpression abolished the suppressing effects of Brucine on RA‐FLS dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of antidiabetic drugs (e.g., biguanides, sulfonylureas, glinides) and herbs/dietary supplement (e.g., AR, Rehmannia glutinosa , Pueraria lobata and their compound preparation) is very popular in clinical practice in some countries (e.g., China, Japan) ( Cui et al, 2018 ; Wu et al, 2021 ; Liu et al, 2023 ). DAPA is frequently co-administrated with some popular antidiabetic herbs (e.g., AR and its compound preparation) in China.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies (2015-2021), CKD patients use traditional medicine alone or in conjunction with conventional medicine (Zhao et al 2021). Current therapies using commercially available drugs, such as ACEIs, angiotensin II receptor blockers and calcium channel blockers, generally only delay the progression of CKD (Wu et al 2021). Therefore, conventional doctors rely on plant-based medicines as a supplementary option to conventional medicine for an array of human ailments (Xego et al 2021).…”
Section: Interactions Between Herbal Medicines and Western Medicinesmentioning
confidence: 99%
“…In some cases, administering the incorrect dosage can result in toxicity.The ability of medicinal plants to boost the body's natural antioxidant defence mechanisms is often responsible for their beneficial effect on kidney disease(Khan et al 2022). Previous studies conducted in patients with CKD in Tanzania, Peru and China found frequent use of medicinal plants(Herrera- Añazco et al 2019;Stanifer et al 2015;Wu et al 2021). However, the characteristics of their use could be different in the South African population because of cultural differences between the countries.…”
mentioning
confidence: 99%